Aplication of Liqu Quese for Light Weight Brick Transportation (Case Study at PT Priority One Indonesia Krikilan No. 28, Driyorejo District, Gresik Regency): (Case Study at PT Priority One Indonesia Krikilan No. 28, Driyorejo District, Gresik Regency) - Febryanto, Indra Dwi; Virdaus, Mokhammad Ivan (Tibuana, 2021)
At the location of public queuing services, there are often many customers lining up to be served immediately. This problem also exists in the process of transporting light bricks at PT. Priority One Indonesia. It is not efficient because of the time they can spend doing more important things. In this case, a technology is needed to make it easier for customers to queue. In this study, a web-based or online queuing application called the LiQu application was designed. The output of the LiQu application system is to make the queuing process can be done online, and to conduct customer satisfaction research on the performance of the light brick transportation queue service at PT. Priority One Indonesia. Then perform 2 analysis tests, namely Usability analysis calculating the results of the questionnaire using the Likert Scale Inteval method and Reliability analysis with WAPT 3.1 software testing then calculations using the Nelson model.